THE INFLUENCE OF DIGITAL LITERACY AND FINANCIAL LITERACY ON THE FINANCIAL BEHAVIOR OF GEN Z ENTREPRENEURS MEDIATED BY ENTREPRENEURIAL CREATIVITY IN THE INDONESIAN YOUNG ENTREPRENEURS ASSOCIATION (HIPMI) Jakarta - Situmorang, Exaudi; Nurjanah, Siti; Sari Wulan, Rd. Tuty (Global Research and Innovation Journal, 2026)
This study aims to determine the effect of digital literacy and financial literacy on the financial behavior of Gen Z entrepreneurs mediated by entrepreneurial creativity in the Indonesian Young Entrepreneurs Association (HIPMI) Jakarta. Primary data was obtained using stratified random sampling method with a sample size of 150 HIPMI Jakarta members through an independent survey with an online questionnaire. This research was conducted using quantitative descriptive method with Structural Equation Modeling Partial Least Squares (SEM-PLS) technique with Smart-PLS application to analyze the data. The results showed that there is a positive and significant effect of digital literacy, financial literacy and entrepreneurial creativity on financial behavior in Gen Z entrepreneurs of the Indonesian Young Entrepreneurs Association, Jakarta. This research is limited to Jakarta and with limited use of variables, namely digital literacy, financial literacy and entrepreneurial creativity. Digital literacy variables include the ability of functional and advanced skills in digital literacy, digital savings and loans, digital security, digital information management, communication and collaboration. Financial literacy variables include general knowledge of finance, savings and loans, insurance, investment. Entrepreneurial creativity variables include creativity, entrepreneurial alertness, proactive personality, determination for innovation, self-leadership and self-efficacy. Financial behaviors include paying bills on time, budgeting for expenses and recording expenses and purchases, provision of unexpected funds, regular savings allocation and price comparison before buying.